Crystal Growth of a New 8H Perovskite Sr8Os6.3O24Exhibiting High TCFerromagnetism - Thakur, Gohil S.; Doert, Thomas; Mohitkar, Shrikant; Schnelle, Walter; Felser, Claudia; Jansen, Martin (Crystal Growth and Design, 2021)
Single crystals of a new twinned hexagonal perovskite compound Sr8Os6.3O24 have been synthesized, and structural and magnetic properties have been determined. The compound crystallizes in a hexagonal cell with lattice parameters a = 9.6988(3) Å and c = 18.1657(5) Å. The structure is an eight-layered hexagonal B-site deficient perovskite with the layer sequence (ccch)2 and represents the first example of a hexagonal structure among 5d oxides adopting a twin option. The sample shows spontaneous ferromagnetic magnetization below 430 K with a small saturation moment of 0.11 μB/Os ion. This is the highest Curie temperature (TC) reported for any bulk perovskite containing only 5d ions at the B site.
CRIS-Team Scopus Importer:2022-04-14